IGFBPs were associated with stemness, inflammation, extracellular matrix remodeling and poor prognosis of low-grade glioma - Liu, Zhihui; Ji, Hang; Fu, Wenchao; Ma, Shuai; Zhao, Hongtao; Wang, Fang; Dong, Jiawei; Yan, Xiuwei; Zhang, Jiheng; Wang, Nan; Wu, Jiasheng; Hu, Shaoshan (Frontiers in Endocrinology, 2022)
Background: The IGFBP family of insulin-like growth factor binding proteins has important biological functions in the organism. However, the role of IGFBP family in low-grade glioma (LGG) has not been fully explored. Methods: We validated the clinical value of the IGFBP family using RNA-seq data and clinical data of LGG in TCGA, and constructed an IGFBPScore using LASSO-regression analysis for prognosis prediction, subtype determination and treatment sensitivity determination. Subsequently, we explored the role of the IGFBP family in the development of LGG using PanCanAtlas data. Results: Our results suggested that most IGFBP family members were aberrantly expressed and were strongly associated with poor prognosis in LGG. By constructing an IGFBPScore representing the IGFBP family, we found that tumor samples with high IGFBPScore had a glioblastoma-like mutation pattern characterized by IDH1wt, EGFRmut, PTENmut and NF1mut with hypo-methylation and glioma stem cell(GSC) diversity. In contrast, the low IGFBPScore group was characterized by IDH1mut accompanied by TP53mut, CICmut and ATRXmut, and had a hyper-methylation status as well as the GSC restriction. In addition, the high-IGFBPScore group had a high inflammation phenotype with increased immune antigenicity and increased infiltration of immune molecules and immune cells, as well as a high extracellular matrix phenotype and enhanced multiple metabolic pathways compared to the immune-quiet phenotype of the low-IGFBPScore group, which were strongly associated with poor prognosis. Conclusion: Our study provides a summary analysis as well as a theoretical basis for the biological role and clinical value of the IGFBP family in LGG, providing an important therapeutic target for LGG.